1972
DOI: 10.1126/science.178.4060.505
|View full text |Cite
|
Sign up to set email alerts
|

Detergent Effects on a Reverse Transcriptase Activity and on Inhibition by Rifamycin Derivatives

Abstract: A reverse transcriptase activity, extracted from virus-transformed cells, is activated by very low concentrations of nonionic detergents. These same detergents also significantly reduce the effectiveness of certain rifamycin derivatives as inhibitors of the polymerase activity when the detergents are present at micelle-forming concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…We also observed that Trition X-100 stimulated the purified enzyme activity with (dT)12_.18 (rA)n as template-primer (Wu, A. M., Cretta, A. & Gallo, R. C., in preparation), confirming the observation made by Thompson et al with partially purified enzymes (12,13). The magnitude of stimulation is proportional to the concentration of template primer and to the time of incubation.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…We also observed that Trition X-100 stimulated the purified enzyme activity with (dT)12_.18 (rA)n as template-primer (Wu, A. M., Cretta, A. & Gallo, R. C., in preparation), confirming the observation made by Thompson et al with partially purified enzymes (12,13). The magnitude of stimulation is proportional to the concentration of template primer and to the time of incubation.…”
Section: Methodssupporting
confidence: 89%
“…The results in Table 3 also show that the concentration of nonionic detergent (Triton) can drastically affect the magnitude of inhibition by various concentrations of rifamycin SV derivatives, confirming the observation first made by Thompson et al (12,13). Presumably, this is because of micelle formation from the detergent and solubilization of the inhibitor into the micelles.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Some restriction enzymes, reverse transcriptases, and Taq polymerases are stabilized by Triton X-100 or NP-40 (Weyant et al, 1990), while some other polymerases are activated by detergents (Thompson et al, 1972;Wu and Cetta, 1975;Hirschman et al, 1978). Triton X-100 is used for purification of HCV RdRp (Weng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Rifazacyclo-16 is the most effective inhibitor of the RNA-instructed DNA polymerase yet tested (ref. 4, and Thompson, F. M., Libertini, L. J., Joss, U. R. & Calvin, M., Biochemistry, submitted), while the others were less active. However, these drugs were all ineffective against viral transformation of mouse cells, presumably because they were unable to penetrate the cell membrane.…”
mentioning
confidence: 97%